Long-run inflation expectations in the ECB survey of professional forecasters: what do the survey responses tell us? - Oinonen S; Viren M (INST ECONOMIC RESEARCH-POLAND, 2022)
Research background: At the background, there are issues related to policy credibility and policy targets. For these issues, long-term forecasts can provide important information. Of course, long-term forecasts are needed also e.g. for evaluation of real returns.Purpose of the article: This paper tries to find out how informative the ECB Survey of Professional Forecasters data on long-term inflation prospects are from the point of view of the overall quality of the survey and on the other hand from the point of view of monetary policy credibility. Methods: The analysis makes use of individual forecaster level quarterly panel data for the period 1999Q1-2018Q4. Conventional panel econometrics tools are used to find out whether forecasts are sensitive to changes in actual inflation and other relevant variables.Findings & Value added: We find some weaknesses considering the size of the survey, the selection of the sample (more precisely the participation to the survey) and the inertial responses of forecasters which suggest that the survey values are not actively updated. Moreover, we find that towards the end of the sample period, the survey values are related to actual inflation and to short-term expectations, which is not consistent with the credibility of the official inflation target.